Literature Review: Impact of Shift Work on Junior Doctors - Ramy Mahmoud Washia (RGUHS National Journal of Public Health, 2025)
Shift work is a fundamental component of junior doctorsrsquo schedules in the UK encompassing long day shifts rotating patterns and regular night duties. Although total working hours have declined due to regulatory frameworks like the European Working Time Directive EWTD the increase in non-standard working hours has raised concerns about its impact on junior doctorsrsquo health and performance. This literature review critically examines the effects of shift work across four key domains physical health mental health clinical performance and work-life balance. Evidence suggests that disrupted circadian rhythms and inadequate rest contribute to short term issues such as fatigue and impaired decision-making as well as long-term risks including cardiovascular disease depression and burnout. Shift work also impairs cognitive function affecting diagnostic accuracy and patient safety. Furthermore irregular schedules negatively influence personal relationships reduce quality time with family and strain work-life integration. Data were gathered from peer-reviewed journals systematic reviews and official reports specifically studies conducted between 2000 and 2024. While numerous interventions-such as optimizing shift rotations and offering psychological support-have been proposed implementation challenges persist due to resource constraints. This review identifies critical knowledge gaps and emphasizes the need for evidence-based reforms in scheduling practices to promote junior doctorsrsquo well-being and sustain healthcare quality.